Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/dech.12754
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Natural Resource Curse: Backward Linkages for Export Diversification and Structural Economic Transformation

Abstract: This article revisits and empirically tests the conjecture that specialization in natural resource industries (NRI) might not necessarily be a ‘curse’ for developing countries if it generates opportunities for export diversification in backward‐linked sectors à la Hirschman. The article systematizes the evolution of the debate around the NRI ‘curse’. Then it empirically tests whether NRI might represent a sufficient ‘domestic representative demand’ à la Linder to favour diversification into backward‐linked sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Concurrently, some studies have reported positive outcomes on income [15], productivity and regional growth [16] resulting from participation in resource-based GVCs. Several studies have also contended that resource-based global value chains foster sectoral growth through backward integration [17]. In a recent study utilizing the OECD-MRIO database, [28] propose that countries specializing in natural resource industries promote high-tech manufacturing exports through backward linkages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concurrently, some studies have reported positive outcomes on income [15], productivity and regional growth [16] resulting from participation in resource-based GVCs. Several studies have also contended that resource-based global value chains foster sectoral growth through backward integration [17]. In a recent study utilizing the OECD-MRIO database, [28] propose that countries specializing in natural resource industries promote high-tech manufacturing exports through backward linkages.…”
Section: Literature Reviewmentioning
confidence: 99%